2021
DOI: 10.3390/s21020529
|View full text |Cite
|
Sign up to set email alerts
|

Walking Secure: Safe Routing Planning Algorithm and Pedestrian’s Crossing Intention Detector Based on Fuzzy Logic App

Abstract: Improving road safety through artificial intelligence is now crucial to achieving more secure smart cities. With this objective, a mobile app based on the integration of the smartphone sensors and a fuzzy logic strategy to determine the pedestrian’s crossing intention around crosswalks is presented. The app developed also allows the calculation, tracing and guidance of safe routes thanks to an optimization algorithm that includes pedestrian areas on the paths generated over the whole city through a cloud datab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 26 publications
1
4
1
2
Order By: Relevance
“…SG extends beyond the context of smart home and will play a major role in the future smart cities ( Lozano Domínguez and Mateo Sanguino Tde, 2021 ), smart factories ( Pech et al, 2021 ), smart retail stores ( Zhang et al, 2019a ), smart rehabilitation labs ( Sessoms et al, 2015 ), and smart devices ( Lozano Domínguez and Mateo Sanguino Tde, 2021 )…”
Section: Smart Gait Devices and Environmentsmentioning
confidence: 99%
“…SG extends beyond the context of smart home and will play a major role in the future smart cities ( Lozano Domínguez and Mateo Sanguino Tde, 2021 ), smart factories ( Pech et al, 2021 ), smart retail stores ( Zhang et al, 2019a ), smart rehabilitation labs ( Sessoms et al, 2015 ), and smart devices ( Lozano Domínguez and Mateo Sanguino Tde, 2021 )…”
Section: Smart Gait Devices and Environmentsmentioning
confidence: 99%
“…Research on active transport has found that an MGB greatly explains pedestrian and cyclist behaviors [ 19 , 20 ]. However, the nature of walking and cycling is changing, with there being greater use of smart app technology; consequently, research on smart apps for active transport has found that they can influence walkers’ and cyclists’ perceptions in a variety of ways [ 21 , 22 , 23 , 24 ]. Nevertheless, despite the importance of green space and motivation for engagement in active transport, research on public green space and extrinsic/intrinsic motivation has been neglected in terms of the role of smart apps for walking and cycling based on goal-directed behavior theory.…”
Section: Introductionmentioning
confidence: 99%
“…iPhone apps enabled reliable evaluations of walking activities [ 23 ]. Users of Google Maps and other apps are able to obtain safer routes for walking and crossing in urban areas [ 21 ]. These results suggest that individuals with high perceived usefulness of smart app for walking and cycling are potentially likely to possess different characteristics from individuals with low perceived usefulness of smart apps for active transport.…”
Section: Introductionmentioning
confidence: 99%
“…On the one hand, among the different actions to reduce the number of pedestrian accidents that are being carried out, some of these actions focus on studies related to the analysis of pedestrian behavior at crosswalks [ 2 , 3 , 4 , 5 ], to try to anticipate their movements, and take them into account when making decisions about braking the vehicle or slowing down its speed in areas likely to be at risk, due to the presence of pedestrians, who could become potential victims. This information is very valuable in terms of paying attention to pedestrian detection and tracking [ 4 ] and also in terms of designing routes to avoid potential risk areas as much as possible [ 5 ].…”
Section: Introductionmentioning
confidence: 99%